Unified analysis of preconditioning methods for saddle point matrices. Issue 2 (4th July 2014) - Axelsson, Owe
Summary Short and unified proofs of spectral properties of major preconditioners for saddle point problems are presented. The need to sufficiently accurately construct approximations of the pivot block and Schur complement matrices to obtain real eigenvalues or eigenvalues with positive real parts and non‐dominating imaginary parts are pointed out. The use of augmented Lagrangian methods for more ill‐conditioned problems are discussed. Copyright © 2014 John Wiley & Sons, Ltd.